Diagnostic accuracy in rotator cuff tears: clinical tests vs MRI - Modipalli, Divakar; Hegde, Atmananda S.; Shetty, Chethan B. (International Journal of Research in Orthopaedics, 2019)
Background: Till date there is a lack of consensus regarding validity of clinical tests in identifying the rotator cuff injuries and also the predictive value of noninvasive investigations done to confirm such shoulder pathology. Methods: We included 48 patients with shoulder complaints in our study who underwent blinded clinical examination and MRI of shoulder, whose findings were compared with arthroscopic findings and were statistically analyzed. Results: In the study group mean age was 47 years and 71% were males. When compared with arthroscopy, clinical examination for supraspinatus had better sensitivity (90) but low specificity and negative predictive value (NPV) (37.5). MRI evaluation of supraspinatus had specificity of 85 and NPV of 60. Infraspinatus had almost similar statistical values. MRI was found to have better specificity (89.5) in comparison with clinical examination (52.6) in subscapularis evaluation along with higher positive (67 vs. 30) and negative predictive value (94 vs. 90). Conclusions: Clinical examination is good in identifying lesion or tear of supraspinatus and subscapularis but may also have false positives, where usage of noninvasive MRI will reduce these false positive in comparison with gold standard arthroscopy. Although clinical examination is very useful for diagnosis of rotator cuff injuries, MRI could be used to improve specificity and predictive values in patients who are planned for surgical management of rotator cuff injury.